2006
DOI: 10.1210/jc.2006-1142
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Improvement in Vasodilatory Function Accompanies Increased Insulin Sensitivity in Obesity and Type 2 Diabetes Mellitus

Abstract: Because vasodilatory dysfunction has been postulated to contribute to insulin resistance, the exercise-induced improvement in vasodilatory function may signify changes in the endothelium that could contribute to the improvement in insulin sensitivity observed after aerobic exercise training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 38 publications
3
58
0
Order By: Relevance
“…Indeed, in obese adults, acetylcholine-stimulated vasodilation was improved after a 10% weight loss induced by diet plus exercise, 39 whereas no significant weight loss was obtained in our study. However, De Filippis et al 4 reported improved vasodilatory response to acetylcholine after an 8-week training program, without any weight change. Their training program at high intensity induced a 27% increase in VO 2 peak, which was greater than the 8% obtained with our lower intensity training program.…”
Section: Effects Of Exercise Trainingmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, in obese adults, acetylcholine-stimulated vasodilation was improved after a 10% weight loss induced by diet plus exercise, 39 whereas no significant weight loss was obtained in our study. However, De Filippis et al 4 reported improved vasodilatory response to acetylcholine after an 8-week training program, without any weight change. Their training program at high intensity induced a 27% increase in VO 2 peak, which was greater than the 8% obtained with our lower intensity training program.…”
Section: Effects Of Exercise Trainingmentioning
confidence: 99%
“…Our result, obtained non-invasively, confirmed several previous pharmacological studies demonstrating blunted agonist-mediated vasodilation in obese subjects. 1,4 Measurement of muscle perfusion and vascular conductance during isolated exercise also provided a good estimate of vasodilatory responsiveness of resistance vessels within working muscles. 14 One major result from the present study was that, irrespective of exercise intensity, obese men exhibited lower BF and vascular conductance than their normal-weight counterparts during a local knee-extensor exercise.…”
Section: Impact Of Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid confounding from the most recent exercise bout, the measurements were Table 1. Health benefits of exercise for overweight and obese persons, independent of changes in body g g weight or body fat p p Glucose metabolism and insulin action Decreased fasting glucose [10] Decreased fasting insulin [7,8,10,11•,19] Increased glucose tolerance [11•,12,16] Increased insulin sensitivity [7-10,11•,12-23,24••,25] Decreased HbA 1c [9] Blood Pressures Decreased resting SBP [9,10,15,[27][28][29][30] Decreased resting DBP [9,10,15,[27][28][29][30] Decreased ambulatory BP [29] Lipids and lipoproteins Decreased cholesterol [14,16,31] Decreased LDL-cholesterol [14,31] Increased HDL-cholesterol [10,23,29,32] Decreased triglycerides [9,10,16,23,29,32] Improved LDL and HDL Subfractions [32] Endothelial function Increased vascular dilatory function [14,35••,36,37] Hemostasis Increased t-PA release capacity [35••] Decreased platelet reactivity [38,39] Enhanced fibrinolysis [38,39] Decreased plasminogen activator inhibitor-1 …”
Section: Glucose Metabolism and Insulin Actionmentioning
confidence: 99%